A general simulation-based study on printability of inks in direct ink writing - Md. Asaduzzaman Sourov; Seyda Islam Emu; Md. Shajedul Hoque Thakur; Maruf Md Ikram; A. K. M. M. Morshed; Muhammad M. Rahman (Scientific Reports)
Abstract Direct ink writing (DIW)-based 3D printing process has gained significant attention due to its ability to accommodate versatile ink materials. However, the most challenging aspect of DIW is the development of inks with suitable printability. To address this, we demonstrate a numerical approach using the finite element method (FEM) to model the printability of inks. Five distinct ink models, including cement, thermoset polymer (epoxy), biopolymer (cellulose nanocrystals), and two hydrogel inks (alginate-based biopolymer and metallic powder), have been chosen to identify the key differentiating characteristics between inks with high and low printability. We focus on the shear thinning behavior, shape retention, and ink blockage region as key factors to evaluate printability and propose a printability grading parameter that demonstrates the qualitative ranking of inks based on their rheology. The study reveals that inks with better printability exhibit greater shear thinning behavior, yield shear strength, shape retention, and viscosity at a suitable inlet pressure. Among all the inks studied, we have found a specific concentration of cellulose nanocrystals (20 wt%) that demonstrates the best printability.